Oxygen Isotopes of Inorganic Phosphate in Environmental Samples Purification and Analysis - Adu-Gyamfi, Joseph; Pfahler, Verena (Springer Nature, 2022)
This open access book distinguished itself from other publications by offering step-by-step instructions on how to extract, purify, provide modifications, and major issues to be encountered during the process. For the δ18OP method to progress, further fundamental research as well as field and laboratory studies need to be conducted for a better understanding of P cycling in the environment. Chapter 1 outlines the background and examples of δ18Op studies in sediments, soils, fresh water, mineral fertilizers, and plants. Chapters 2 and 3 examine the stepwise extraction and purification protocols including reagents, equipment and consumables and preparations for analyses. Chapter 4 examines some of the challenges and modifications during the purification process. Chapter 5 discusses planning and designing of a study using δ18Op, external quality assurance with an example of an inter-laboratory study. Chapter 6 outlines the conclusions, future trends, and opportunities, the scaling out of the method from laboratory to field studies. It is expected that the δ18OP would be extensively applied in research geared to understand phosphorus dynamics in different agro-environments.